1,3-dipolar cycloaddition of CS2 to the coordinated azide in the cyclopalladated [Pd(bzan)(mu-N-3)](2). Crystal and molecular structure of di(mu-N,S-1,2,3,4-thiatriazole-5-thiolate)bis[(benzylideneaniline-C-2,N)palladium(II)] - Santana, A. M.; Mauro, A. E.; Almeida, E. T. de; Netto, A. V. D.; Klein, S. I.; Santos, R. H. D.; Zoia, J. R. (Gordon Breach Publishing, Taylor & Francis Group, 2001)
The compound [Pd(bzan)(mu -N-3)](2) 1, bzan = benzylideneaniline, was prepared from [Pd(bzan) (mu -OOCCH3)](2) by an anion exchange reaction. The 1,3-dipolar cycloaddition of carbon disulfide to the bridged coordinated azide in the cyclometallated compound I was investigated. The species resulting from this reaction, di(mu -N,S-1,2,3,4-thiatriazol-5-thiolate)bis[(benzylideneaniline)palladium(II)] 2, was characterized by IR spectroscopy and X-ray diffraction. The compound 2 is a dimer containing two [Pd(benzylideneaniline)] moieties connected by two vicinal bridging N,S-1,2,3,4-thiatriazole-5-thiolate anions in a square-planar coordination geometry for the palladium atoms.
Keywords: cyclopalladated; azido; cycloaddition; carbon disulfide; infrared spectroscopy; X-ray diffraction